Shadow Banking and Traditional Bank Lending: The Role of Implicit Guarantees - Lucyna Gornicka (Tinbergen Institute, 2014)
Bank holding companies (BHCs) invest in risky projects through bank entities or sell projects for a fee, thus engaging in shadow banking. BHCs can increase their fee income by guaranteeing sold projects with a recourse to the bank's balance sheet. When the expected guarantee repayments depend on total bank proceeds (high capital requirements), BHCs have incentives to increase their bank investments to raise the demand for offbalance projects. The amount of credit in the economy increases, bank defaults are more frequent, and the costs of deposit insurance increase. BHCs with large banks offer higher guarantees than BHCs with small banks, and they dominate the shadow banking sector.
Keywords: G21; G23; G28; 330; shadow banking; implicit recourse; special purpose vehicles